Self Concept of Kery Astina as A Paradoy Youtuber - Adi, Achwan Noorlistyo; Putri, Shinta Hartini; Sadiyyah, Zulfanida Nurul (Yayasan Sinergi Kawula Muda, 2023)
A self-concept is very important in creating work which is now very easy with social media. By having a self-concept, a person can increase his self-confidence. This self-concept also influences the consistency and existence of someone who focuses on creating work through social media such as YouTube. The purpose of this research is to find out Kery Astina's motives for becoming a YouTuber, to find out Kery Astina's experience in forming his virtual identity, and to find out the meaning of subscribers for Kery Astina. Researchers used qualitative methods with a phenomenological approach. Data obtained using in-depth interviews and direct observation. The results of this research show that Kery Astina has past and future motives in forming her concept as a parody YouTuber. Apart from that, the experience of forming this parody self-concept created his image as a comedian and he felt proud of what he had achieved after becoming a parody YouTuber. Kery Astina interprets his subscribers as assets because of his money-oriented principle when he sees that the YouTube platform can make money. This research can add to the body of communication science, especially on cyber culture in the current digital era.